GE_GERICHTE A/2472/2005 vom 26. Mai 2005 - GE Cour de justice (2005)
; PRÉVOYANCE PROFESSIONNELLE ; PARTAGE(SENS GÉNÉRAL) ; CONVENTION DE PARTAGE ; DIVORCE ; JUGEMENT DE DIVORCE ; TRANSACTION(ACCORD) ; INTERPRÉTATION(SENS GÉNÉRAL) | CC.141; CC.142; CC.122.1